Toxic metabolites, MAPK and Nrf2/Keap1 signaling pathways involved in oxidative toxicity in mice liver after chronic exposure to Mequindox - Liu, Qianying; Lei, Zhixin; Huang, Anxiong; Wu, Qinghua; Xie, Shuyu; Awais, Ihsan; Dai, Menghong; Wang, Xu; Yuan, Zonghui (Scientific reports, 2017)
Mequindox (MEQ) is a synthetic antimicrobial agent of quinoxaline-1,4-dioxide group (QdNOs). The liver is regarded as the toxicity target of QdNOs, and the role of N → O group-associated various toxicities mediated by QdNOs is well recognized. However, the mechanism underlying the in vivo effects of MEQ on the liver, and whether the metabolic pathway of MEQ is altered in response to the pathophysiological conditions still remain unclear. We now provide evidence that MEQ triggers oxidative damage in the liver. Moreover, using LC/MS-ITTOF analysis, two metabolites of MEQ were detected in the liver, which directly confirms the potential connection between N → O group reduction metabolism of MEQ and liver toxicity. The gender difference in MEQ-induced oxidative stress might be due to adrenal toxicity and the generation of M4 (2-isoethanol 1-desoxymequindox). Furthermore, up-regulation of the MAPK and Nrf2-Keap1 family and phase II detoxifying enzymes (HO-1, GCLC and NQO1) were also observed. The present study demonstrated for the first time the protein peroxidation and a proposal metabolic pathway after chronic exposure of MEQ, and illustrated that the MAPK, Nrf2-Keap1 and NF-кB signaling pathways, as well as the altered metabolism of MEQ, were involved in oxidative toxicity mediated by MEQ in vivo.
Keywords: játra; Oxidative Stress; oxidační stres; Kelch-Like ECH-Associated Protein 1; oxidace-redukce; Female; NF-E2-Related Factor 2; Anti-Infective Agents; antiinfekční látky; zvířata; myši; Mice; ženské pohlaví; Liver; Male; faktor 2 související s NF-E2; MAP Kinase Signaling System; Oxidation-Reduction; Quinoxalines; Animals; mužské pohlaví; chinoxaliny; KEAP-1; MAP kinasový signální systém